Distinguishing epidemiological features of the 2013–2016 West Africa Ebola virus disease outbreak. Issue 3 (2nd July 2016) - Shultz, James M.; Espinel, Zelde; Espinola, Maria; Rechkemmer, Andreas
ABSTRACT: The 2013–2016 West Africa Ebola virus disease epidemic was notable for its scope, scale, and complexity. This briefing presents a series of distinguishing epidemiological features that set this outbreak apart. Compared to one concurrent and 23 previous outbreaks of the disease over 40 years, this was the only occurrence of Ebola virus disease involving multiple nations and qualifying as a pandemic. Across multiple measures of magnitude, the 2013–2016 outbreak was accurately described using superlatives: largest and deadliest in terms of numbers of cases and fatalities; longest in duration; and most widely dispersed geographically, with outbreak-associated cases occurring in 10 nations. In contrast, the case-fatality rate was much lower for the 2013–2016 outbreak compared to the other 24 outbreaks. A population of particular interest for ongoing monitoring and public health surveillance is comprised of more than 17, 000 "survivors, " Ebola patients who successfully recovered from their illness. The daunting challenges posed by this outbreak were met by an intensive international public health response. The near-exponential rate of increase of incident Ebola cases during mid-2014 was successfully slowed, reversed, and finally halted through the application of multiple disease containment and intervention strategies.